Maternal Magnesium Deficiency in Mice Leads to Maternal Metabolic Dysfunction and Altered Lipid Metabolism with Fetal Growth Restriction - Gupta, Madhu (ScholarOne, 2014)
Inadequate magnesium (Mg) intake is a widespread problem, with over 50% of women of reproductive age consuming less than the Recommended Dietary Allowance (RDA). Because pregnancy increases the requirement for Mg and the beneficial effects of magnesium sulfate for preeclampsia/eclampsia and fetal neuroprotection are well described, we examined the outcomes of Mg deficiency during pregnancy. Briefly, pregnant Swiss Webster mice were fed either control or Mg-deficient diets starting on gestational day (GD) 6 through euthanasia on GD17. Mg-deficient dams had significantly reduced weight gain and higher plasma adipokines, in the absence of inflammation. Livers of Mg-deficient dams had significantly higher saturated fatty acids (SFAs) and monounsaturated fatty acids (MUFAs) and lower polyunsaturated fatty acids (PUFAs), including docosahexaenoic acid (DHA) (P < 0.0001) and arachidonic acid (AA) (P < 0.0001). Mechanistically, Mg deficiency was accompanied by enhanced desaturase and elongase mRNA expression in maternal livers along with higher circulating insulin and glucose concentrations (P < 0.05) and increased mRNA expression of Srebf1 and Chrebp, regulators of fatty acid synthesis (P < 0.05). Fetal pups exposed to Mg deficiency were growth-restricted and exhibited reduced survival. Mg-deficient fetal livers showed lower MUFAs and higher PUFAs, with lower desaturase and elongase mRNA expression than controls. In addition, DHA concentrations were lower in Mg-deficient fetal brains (P < 0.05). These results indicate that Mg deficiency during pregnancy influences both maternal and fetal fatty acid metabolism, fetal growth and fetal survival, and support better understanding maternal Mg status before and during pregnancy.